STUDY REGARDING THE IMPACT OF SPORT COMPETITIONS ON STUDENTS SOCIALIZATION - Sabin, Sopa Ioan; Marcel, Pomohaci (European Scientific Journal, ESJ, 2014)
Sport activities are considered to be the perfect setting in training young generations, being appreciated as an important socializing factor with increasingly higher value in modern society. Sport competitions does not only prove who is the best team or player, but are ways of bringing the sportives together to compete, know each other, socialize and make friends. Using the observation method and the questionnaire method, we tried to analyze the impact of sport competition on students socialization level. We build up a questionnaire using 15 items and applied it on the teams that participated in the 4th edition of mixed volleyball competition for students known as “Cupa Primăverii”. However, this competition was reserved for students from the University “Lucian Blaga”, Sibiu. The results showed us that students participated in this kind of activities to compete with others, play volleyball, make friends and socialize.